f(x)=3x-5, g(x)= 2x+3. Rezolvați ecuația 2×f(x)+3×g(x)=7
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
2×f(x)+3×g(x)=7
2(3x-5)+3(2x+3)=7
6x-10+6x+9=7
12x-1=7
12x=8
x=8/12
x=2/3
F(x)=3x-5
f(2/3) =2/3×3-5
f(2/3)=2-5
f(2/3)=-3
g(x)= 2x+3
g(2/3)=2/3×2+3
g(2/3)=4/3+3
Amplificam 3 cu 1/3
g(2/3)=4/3+9/3
g(2/3)=13/3
Explicație pas cu pas:
Alte întrebări interesante
Limba română,
8 ani în urmă
Geografie,
8 ani în urmă
Chimie,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă